Confessio Tetrapolitana: En augsburgsk bekendelse mellem Luther og Zwingli - Dreyer, Rasmus H.C. (Dansk Teologisk Tidsskrift, 2019)
This article introduces one of the alternative reformatory confessions from the Diet of Augsburg 1530, the Confessio Tetrapolitana (CT). Due to the disagreement with the Saxonian/Lutheran party at the Diet, the German imperial cities of Strasbourg, Konstanz, Memmingen and Lindau delivered their own account of faith written by the Strasbourg theologians Martin Bucer and Wolfgang Capito. The article describes the historical background and the political and theological position of Strasbourg and its envoys at the Augsburg Diet. A structural comparison between CT and Melanchthon’s Confessio Augustana (CA) leads to a detailed summary of the 23 articles and an investigation of the confession’s theological characteristics: 1) Its Biblicism. 2) The vagueness of the Eucharistic article (article 18). 3) The new life of the Christian and 4) the consequences regarding the community as a Christian societas. Through these paragraphs, it becomes clear that The Tetrapolitan Confession represents a typical theology of the Humanist reformation movement. On the one hand, it resembles the theology of Melanchthon in CA and the early writings of Zwingli, yet on the other hand, it differs from Zwingli’s confession of The Diet of Augsburg, his personal confession, Fidei Ratio. Thus, CT is an expression of Bucer’s theological standpoint, which is again rooted in the Strasbourg Humanist milieu with its Zwingli-inspired urban reformation theology. The article ends with a brief study of connections between Bucer and the Danish reformation both in terms of personal relations and theological similarities.